(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The Foreigner and His Image in Meiji Japan (1868 - 1912) Meiji Japan (1868 - 1912) remains as the embodiment of radical changes that took place in a very short time. Ali the specialists seem to agree on placing Meiji Japan at the top of a list of victors, both within borders and outside them. As far as other nations are concerned, only a few could be proud of such a radical social, cultural, economical), military and politically change in less than fifty years. Japan's evolution from a politically and economically isolated country to a modem and open one is very interesting for us, the Romanians that underwent a similar experience after 1989. Meiji Japan could be seen as a model of transition in an efficient way from a closed society to an open one. A very painstaking effort that the governors took in the nineteenth century Japan was the construction of a strong identity. It was necessary for a nation that wanted to be included in the family of modem countries to find a distinct mental and material shape so that it could be included as a unique voice. ln drawing it the Japanese governors used the foreigners. Sometimes their image was stronger than the people themselves. The immediacy of the foreigners still remains a fact. Fancied or real, the foreigners played a very important role in Modem Japan's new identity. As foreigners played such an important part in developing the modem Japanese society that everybody has esteemed ever since, I considered them a very good theme for this paper. The presence of these others in Japan's history seems to be very significant. The Ainu gave credit to the real leader in Japan - the Shogun. The Mongols' trials to invade Japan triggered off The Emperor's cult in the thirteenth century. The Westemers who arrived in Japan in the sixteenth century helped Nobunaga and Hideyoshi make peace in Japan. Nineteenth century foreigners' presence made Japan feel like redefining itself. Scarce and short timed as it may be - the presence of foreigners is very strongly perceived by the natives. We also have to talk about the cultural and economica! emulation of China. A very scarce enumeration of foreign influences, as well as the presentation of the Japanese people's mind in the nineteenth century stand for the fact that the other helps one to redefine better and sometimes quicker than expected. As difficult to believe, as it may seem, the access to one's own values and cultural traditions is sometimes accelerated and even restored by a foreign presence. The present paper is a very short study of such a case. The presence of foreigners, emulating their values, making conscious of the differences between them, the dynamics of the source of influences and ideas (Alter) and the recipient (Ego, that is the Japanese) are treated here as well. As far as changing one's roind regarding foreigners, the cases of Inoue Tetsujiro and Yukichi Fukuzawa seemed to be the most interesting ones. So I introduced them as study cases.